Comparative study of rabbit sino-atrial node cell models - Garny, A; Noble, P; Kohl, P; Noble, D (2002)
This paper compares recent mathematical models of rabbit sino-atrial node pacemaker cell activity [Cellular and Neuronal Oscillators, Dekker, New York, 1989, p. 59; Am. J. Physiol. 266 (1994) C832; J. Theor. Biol. 181 (1996) 245; Am. J. Physiol. 279 (2000) H397] and evaluates them with the perspective of developing detailed multicellular models of the right atrium. (i) All evaluated models reproduce control action potential shapes, which have been recorded experimentally (although one of them (Dokos et al., loc. cit.) shows an unusually long spontaneous diastolic depolarisation phase, probably more compatible with room-temperature rather than body-temperature conditions). This is achieved on the basis of implementing sarcolemmal ion fluxes as a function of (computed) internal and (computed/fixed) external ion concentrations. Also, all models address, to some extent, intracellular calcium handling processes. (ii) Application of the various models to simulated experimental interventions (such as block of selected ion currents) reveals a wide range of responses (partially outside patho-physiologically plausible ranges) and inconsistencies between simulated and experimental data, thus defining the need for further model improvement. (iii) The heterogeneity of cell parameters within the sino-atrial node is addressed only by one of the models (Zhang et al., loc. cit.). (iv) Computation time differs greatly between the various models, with a ratio of 1:6 between the slowest and the fastest models. We conclude that, out of the currently available set, the Zhang et al. (loc. cit.) model is best suited for application to multicellular modelling of the right atrium. © 2002 Published by Elsevier Science Ltd.